(untitled) (American Journal of Islam and Society, 2001)
The problems and challenges of the twenty-fmt century will force world religions to play a more meaningful role in society and civilization. By subjecting human reason to transcendental truths and spiritual guidance, religion serves a a powerful molder of wholesome, balanced and coherent personality, culture and civilization. Legislation alone is inadequate to combat the serious moral corruption in institutions and systems. The state will also have to make room for the expansion of religlon-based ethics and spiritual values into business, international trade, media, judiciary and politics. The continued separation of spiritual values from worldly affairs is not only untenable from a holistic perspective of man but would ultimately be dhtrous to human civilization. A pervasive ethical consciousness, engendered by a tawhidic worldview, is greatly needed a panacea to the crisis of contemporary society.